A calibration procedure for two-dimensional laboratory-scale hybrid finite–discrete element simulations. (April 2015) - Tatone, B.S.A.; Grasselli, G.
Abstract: In recent years, Bonded-Discrete element methods (Bonded-DEM) and hybrid finite–discrete element methods (FDEM) have become widely employed to model brittle fracturing processing in geomaterials. These approaches possess the ability to explicitly simulate fracture and fragmentation, but necessitate a large number of input parameters to be specified. Many of these parameters cannot be directly measured or characterized via laboratory tests and therefore must be estimated via calibration procedures to attain reliable results. In this work, a prescriptive procedure to arrive at a combination of input parameters for the newly developed Y-Geo FDEM code is developed. The proposed procedure is applicable for laboratory-scale simulations where some laboratory testing data for the material to be simulated is available. It uses a combination of the known elastic parameters, uniaxial compressive strength, and Brazilian disc strength of a material as calibration targets and limits the over-determined nature of the calibration problem by considering the similitude of the resulting fracture patterns. The development of this procedure represents a major step forward in obtaining reliable and consistent results using an FDEM approach. Abstract : Highlights: Principles of the combined finite–discrete element method (FEM–DEM) are reviewed. New calibration procedure for lab-scale simulations is developed. Over-determined nature of the calibration problem is identified and addressed. Validity of advanced numerical methods and importance of calibration are discussed. Associated computational demands are presented.